Not a Lucky Break? Why and When a Career Hiatus Hijacks Hiring Chances - Liam D'hert; Louis Lippens; Stijn Baert (Institute of Labor Economics (IZA), 2024)
Sustaining social security systems amidst an ageing population requires (re)integrating the unemployed and inactive into work. However, stigma surrounding non-employment history can create barriers to finding a job. Whilst unemployment stigma is well-documented, inactivity stigma remains under the radar. To address whether, why, and when inactivity hinders hiring, we employed a vignette experiment where real-life recruiters rated fictitious applicants with varying non-employment breaks on hireability and productivity. Results reveal employers rank candidates by their reason for being out of work: those with training breaks rank highest, followed by former caregivers, the previously ill and the unemployed, and last, the discouraged. Productivity perceptions match this pattern. Trainees score highest for skills, motivation, cognition, discipline, reliability, flexibility, and trainability. Caregivers excel in perceived social skills but fall short on flexibility. The previously ill are seen as more motivated than the unemployed but likely raise health concerns. The discouraged trigger the harshest stigma, particularly for motivation and self-discipline. Longer lapses hurt hiring chances, but not for training breaks.
Keywords: C91; E24; J21; J64; 330; career break; unemployment; inactivity; hiring chances; factorial survey experiment